Quantifying the quality and sampling time of oil and grease in urban stormwater runoff - Chow M.F.; Yusop Z. (Springer Verlag, 2023)
Housing; Land use; Pollution; Runoff; Storm sewers; Storms; Correlation analysis; Event mean concentrations; Oil and grease; Sampling strategies; Sampling time; Stormwaters; Tropical countries; Urban stormwater runoff; Catchments